Right Forceps Minor and Anterior Thalamic Radiation Predict Executive Function Skills in Young Bilingual Adults - Mamiya, Ping C.; Richards, Todd L.; Kuhl, Patricia K. (Frontiers in Psychology, 2018)
Executive function (EF) skills enhance learning across domains, and are particularly linked to the acquisition of a second language. Previous studies have shown that bilingual individuals show enhanced EF skills in cognitive tasks where they attended a targeted dimension of a stimulus while inhibiting other competing cues. Brain imaging revealed that bilingual young adults’ performances in the Stroop color-naming task were related to the volume of anterior cingulate cortex (ACC) and inferior frontal lobe. Subjects who had greater white-matter in the frontal cortex showed enhanced performances in the same task, suggesting that brain fiber pathways connecting ACC to the frontal region may be related to the Stroop color-naming task. No studies to date have examined the tissue properties of brain fiber pathways connecting these brain regions and their association with subjects’ EF performance. Importantly, there are no data establishing whether bilingual subjects exhibit different reaction times when words are presented in their first versus second language. To study these questions, we used behavioral and unbiased whole-brain analyses, recruiting 21 Chinese students. Using the Stroop color-naming task, we measured subjects’ reaction times (RTs) in which color names were displayed using fonts that matched the named color (congruent task) or mismatched the color (incongruent task). Subjects performed the task twice, first in English, subjects’ second language, then in Chinese, subjects’ primary language. Results from whole-brain analysis showed that students’ RT in both the English and Chinese tasks were significantly correlated with the mode of anisotropy (MO) in a brain cluster containing the forceps minor and anterior thalamic radiation in the right hemisphere. We also found that fractional anisotropy (FA) significantly predicted subjects’ RT, with higher FA predicting shorter RT. Taken together, our findings demonstrate that right forceps minor and anterior thalamic radiation predict EF skills, suggesting that this brain feature may be important for young bilingual adults using their first and second languages to direct their attention when conflicting cues are present.